2007
DOI: 10.1111/j.1467-9515.2007.00553.x
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Multidisciplinary Systematic Reviewing: A Study on Social Exclusion and Mental Health Policy

Abstract: In the clinical sciences, systematic reviews have proved useful in the aggregation of diverse sources of evidence. They identify, characterize and summate evidence, but these methodologies have not always proved suitable for the social sciences. We discuss some of the practical problems faced by researchers undertaking reviews of complex and cross-disciplinary topics, using the example of mental health and social exclusion. The barriers to carrying out social science and cross-disciplinary reviews are reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 47 publications
0
22
0
1
Order By: Relevance
“… Publications ( n = 66, 58 controlled trials, 8 systematic reviews) Standard search in multiple databases; no dates reported Australia Aggregated above Methodology ( n = 5) Chapman, 2013 [ 31 ] To identify gaps and priorities in the maternal health research, generate a list of maternal health research questions… and adapt questions… to create research questions for use in a future prioritization exercise with experts and other stakeholders. Systematic reviews ( n = 178) Searched the Cochrane Database of Systematic Reviews; 2006–2011 USA Li et al 2012, Nasser et al 2007, de Vet et al 2001, Clarke et al 2007 Curran, 2007 [ 33 ] What empirical evidence is available on the relationships between mental health problems and social exclusion? What is the nature of this evidence?…”
Section: Resultsmentioning
confidence: 99%
“… Publications ( n = 66, 58 controlled trials, 8 systematic reviews) Standard search in multiple databases; no dates reported Australia Aggregated above Methodology ( n = 5) Chapman, 2013 [ 31 ] To identify gaps and priorities in the maternal health research, generate a list of maternal health research questions… and adapt questions… to create research questions for use in a future prioritization exercise with experts and other stakeholders. Systematic reviews ( n = 178) Searched the Cochrane Database of Systematic Reviews; 2006–2011 USA Li et al 2012, Nasser et al 2007, de Vet et al 2001, Clarke et al 2007 Curran, 2007 [ 33 ] What empirical evidence is available on the relationships between mental health problems and social exclusion? What is the nature of this evidence?…”
Section: Resultsmentioning
confidence: 99%
“…We define social inclusion in relation to the right to full participation in society espoused through the United Nations Convention on the Rights for Persons with Disabilities (UNCRPD) [4]. That is, social inclusion involves feeling accepted, having individual and collective agency to determine participation, and the removal of structural and attitudinal barriers to participation [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Within the extant literature, general principles for conducting an evidence map have been articulated [2,11,12] and are summarized in Table 1. The following sections provide an example of how these principles can be operationalized, in this instance, drawing on the experience of generating an evidence map for interventions in youth mental‐health disorders.…”
Section: Mapping Methodology: Illustrating Key Principlesmentioning
confidence: 99%